Plasma Diagnostics in Reactive High-Power Impulse Magnetron Sputtering System Working in Ar + H2S Gas Mixture; Coatings; Vol. 10, iss. 3 - Hubicka Z.; Cada M. Martin; Kapran A. Anna; Olejnícek J. Jiri; Ksírová P.; Zanaska M.; Adamek P.; Tichy M. Milan (2020, 2020)
Title screen